All-cellulose functional membranes for water treatment: Adsorption of metal ions and catalytic decolorization of dyes. (15th July 2021) - Georgouvelas, Dimitrios; Abdelhamid, Hani Nasser; Li, Jing; Edlund, Ulrica; Mathew, Aji P.
Graphical abstract: Highlights: All-cellulose layered membranes were developed using micro and nanoscaled cellulose. Zwitterionic polymer grafted cellulose nanocrystals provided pH specific charge. Adsorption of metal ions and dyes attributable to active sites on nanoscaled cellulose. Membranes act as metal-free catalysts for the decolorization of dyes via hydrogenation. Abstract: In this study, we present a facile, one-step method for the manufacturing of all-cellulose, layered membranes containing cellulose nanocrystals (CNC), TEMPO (2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical)-mediated oxidized cellulose nanofibers (TO-CNF), or zwitterionic polymer grafted cellulose nanocrystals (CNC- g -PCysMA) as functional entities in combination with cellulose fibers and commercial grade microfibrillated cellulose. The presence of active sites such as hydroxyl, carbonyl, thioethers, and amines, gave the membranes high adsorption capacities for the metal ions Au (III), Co (II), and Fe (III), as well as the cationic organic dye methylene blue (MB). Furthermore, the membranes served as excellent metal-free catalysts for the decolorization of dyes via hydrogenation. A 3-fold increase of the hydrogenation efficiency for cationic dyes such as rhodamine B (RhB) and methylene blue was obtained in the presence of membranes compared to NaBH4 alone. Water-based processing, the abundance of the component materials, and the multifunctional characteristics of the membranes ensure their potential as excellent candidates for water purification systems.